Chronic Stress Promotes Cancer Development - Dai, Shirui; Mo, Yongzhen; Wang, Yumin; Xiang, Bo; Liao, Qianjin; Zhou, Ming; Li, Xiaoling; Li, Yong; Xiong, Wei; Li, Guiyuan; Guo, Can; Zeng, Zhaoyang (Frontiers in Oncology, 2020)
Background: In real life, people will inevitably encounter stress from various sources. Chronic stress on account of reasons like adversity, depression, anxiety, or loneliness/social isolation, can endanger human health. Recent studies have shown that chronic stress can induce tumorigenesis and promote cancer development. This review describes the latest progress of research on the molecular mechanisms by which chronic stress promotes cancer development. Findings: Primarily, chronic stress activates the classic neuroendocrine system (the hypothalamic-pituitary-adrenal (HPA) axis) and the sympathetic nervous system (SNS), which is further exacerbated by the decline and dysfunction of the prefrontal cortex and the hippocampus under stress. Stress hormones produced during the activation of both the HPA axis and the SNS can promote tumorigenesis and cancer development through a variety of mechanisms. Chronic stress can also cause corresponding changes in the body's immune function and inflammatory response, which is significant because a long-term inflammatory response and the decline of the body's immune surveillance capabilities are implicated in tumorigenesis. Conclusions: Stress management is of great importance to both healthy people and cancer patients. Whether drugs that limit the signaling pathways downstream of the HPA axis or the SNS can inhibit cancer progression, prolonging patient survival, or suppress chronic stress-induced cancers, deserves further study.